Adaptive Service Placement, Task Offloading and Bandwidth Allocation in Task-Oriented URLLC Edge Networks - Van Huynh, Dang; Nguyen, Van-Dinh; Dobre, Octavia A.; Khosravirad, Saeed R.; Duong, Trung Q. (IEEE International Conference on Communications (2003), 2023)
Recently, the advances of low-latency communication technologies and edge intelligence have enabled a wide range of task-oriented time-sensitive applications. This paper aims at designing adaptive service placement, task offloading, and bandwidth allocation for ultra-reliable and low-latency communication (URLLC)-aided edge networks. The main objective is to minimise both the total end-to-end (e2e) latency and number of installed services at edge servers. The optimal solutions are obtained by jointly optimising service placement decisions, task offloading portions and bandwidth allocation at dynamic timescales subject to network budgets and application requirements under uncertain environment. Selective simulation results are provided to validate the effectiveness of the proposed solution in term of reducing the latency as well as optimising service placement decisions.